Karakteristik Fisik, Kimia dna Organoleptik Puanchi Bar : Snack Bar Berbasis Pangan Lokal dengan Variasi Formulasi Tepung Ikan Gabus - Fitri, Ika Rahma; Arinda, Ditia Fitri; Sari, Indah Purnama; Ningsih, Windi Indah Fajar; Ramadhani, Ira Dewi (ARGIPA (Arsip Gizi dan Pangan), 2023)
In order to achieve quality standards that are fit for consumption, food quality evaluation evaluates the quality of food ingredients that have undergone processing or cooking. A snack bar called Puanchi Bar was created by using local ingredients in its production, including red mold rice, snakehead fish, and puan sugar. The study was conducted to ensure that Puanchi Bar is practical and complies with established criteria. A laboratory test employing tools and a triangle test are utilized in the physical and chemical characteristic tests to determine whether or not there is a difference between the three formulations. Tests were carried out on 3 selected formulas namely F3, F6, and F9. In the texture and color tests there were insignificant differences but in the moisture content and ash content there were significant differences in the three formulations. In testing conducted in laboratories, Puanchi Bar F3 was shown to have the best texture, color, moisture content, and ash content while still meeting the criteria. Based on aroma, texture, and color factors, the Puanchi Bar F3 formula was the most distinctive and popular among the 18 panelists, according to the findings of the triangle test. It may be said that Puanchi Bar F3 is the best formula in terms of physical characterization, chemical characterization, and the result of the triangle test.